Validitas Petunjuk Praktikum Ekologi: Meningkatkan Kualitas Pembelajaran Berbasis Lingkungan - Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This research aims to determine the validity of ecology practicum instructions. This type of research is development research using the 4D model (Define, Design, Develop, and Disseminate). However, this research modified it to 3D, namely Define, Design, and Develop. The research instrument used was a validation sheet. The data analysis technique used is the percentage technique. The research showed that the validation results from content/material experts were 77%, in terms of appearance it was 75%, and in terms of language it was 87%. Thus, it can be concluded that the ecology practicum instructions are declared valid and do not need to be revised.